Transdermal Delivery of High Molecular Weight Antibiotics to Deep Tissue Infections via Droplette Micromist Technology Device (DMTD) - Lakshmi Pulakat; Howard H. Chen; Madhavi P. Gavini; Lauren A. Ling; Yinian Tang; Alexander Mehm; Gregory L. Martin; Corinna N. Beale; Brian P. Mooney; Hongmin Sun (MDPI AG, 2022)
Wound infection by multidrug-resistant (MDR) bacteria is a major disease burden. Systemic administration of broad-spectrum antibiotics colistin methanesulfonate (CMS) and vancomycin are the last lines of defense against deep wound infections by MDR bacteria. However, systemic administration of CMS and vancomycin are linked to life-threatening vital organ damage. Currently there are no effective topical application strategies to deliver these high molecular weight antibiotics across the stratum corneum. To overcome this difficulty, we tested if high molecular weight antibiotics delivered by Droplette micromist technology device (DMTD), a transdermal delivery device that generates a micromist capable of packaging large molecules, could attenuate deep skin tissue infections. Using green fluorescent protein-tagged E. coli and live tissue imaging, we show that (1) the extent of attenuation of deep-skin E. coli infection was similar when treated with topical DMTD- or systemic IP (intraperitoneal)-delivered CMS; (2) DMTD-delivered micromist did not spread the infection deeper; (3) topical DMTD delivery and IP delivery resulted in similar levels of vancomycin in the skin after a 2 h washout period; and (4) IP-delivered vancomycin was about 1000-fold higher in kidney and plasma than DMTD-delivered vancomycin indicating systemic toxicity. Thus, topical DMTD delivery of these antibiotics is a safe treatment for the difficult-to-treat deep skin tissue infections by MDR bacteria.